Banjarharjo 1 Branding as a Media Based Bamboo Craftsman Village - Iswanto Suwarno; Omar Tanane; Israa Al_barazanchi; Irfan Ahmad; Manvender Kaur Sarjit Singh (Peneliti Teknologi Teknik Indonesia, 2022)
Banjarharjo 1 is one of the hamlets in Muntuk Village, Dlingo District, Bantul Regency. Geographically, Muntuk Village is a village located in an area that is in the highlands. It can be seen from the typology of Banjarharjo 1 hamlet, namely bamboo plantations, rosewood tree plantations, rice fields, farming, and small industries. So most of the livelihoods of Dusun Banjarharjo residents are bamboo craftsmen, but some of them raise animals. Based on the livelihoods of the residents in the Bajarharjo 1 hamlet, the hamlet has potential in various fields such as the potential for human resources, namely bamboo craftsmen and natural resources, namely sonokeling trees. This community service focuses on the branding strategy carried out by the service team in an effort to develop the Bajarharjo hamlet. The branding strategy carried out has the main goal of being known to the wider community and having a place in the minds of the community as well as to attract people to come and enliven the Banjarharjo hamlet again, then the ultimate goal is to make a transaction. This research on branding strategy refers to the theory of Brand Communication and this research is a qualitative research that uses a descriptive method to analyze a found fact. The team conducted interviews with several informants to obtain the required information and made observations at the location of the Bajarharjo hamlet to see the conditions firsthand and observe the media used in branding. The branding strategy efforts that have been carried out by the Bajarharjo hamlet and the UMY service team are still not optimal because there are several aspects of the branding strategy that have not been implemented optimally and have not even been implemented at all. So that currently the condition of the Bajarharjo hamlet is still empty of visitors and the people are still not interested in coming even many people do not know about the information from the hamlet.